2021
DOI: 10.3390/su13074011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Alkanolamine Blends for Carbon Dioxide Absorption. Corrosion and Regeneration Studies

Abstract: There are a lot of research programs focusing on the development of new solvents for carbon dioxide capture. The most important priority should be reducing the energy consumption needed at the regeneration step, but minimizing solvent degradation and its corrosivity is also considered as a priority. In this research, the aqueous blends of 2-amino-2-methyl-1-propanol (AMP: 1 kmol·m−3) and 1-amino-2-propanol (MIPA: 0.1–0.5 kmol·m−3) are characterized in terms of density, viscosity, and surface tension. The carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…An amount of 5 wt.% DEA and AMP showed a moderate value in which the absorbent degraded by 77.48% and 64.02%. Although Equations 1 and 2 show that MEA, DEA, and AMP can produce carbamate and bicarbonate ions, the rates of CO2 absorption capacity are different [32,33]. It is contrary to TEA, which barely degraded (43%) because of its symmetric structure [33].…”
Section: Degradation Of Alkanolamine Absorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…An amount of 5 wt.% DEA and AMP showed a moderate value in which the absorbent degraded by 77.48% and 64.02%. Although Equations 1 and 2 show that MEA, DEA, and AMP can produce carbamate and bicarbonate ions, the rates of CO2 absorption capacity are different [32,33]. It is contrary to TEA, which barely degraded (43%) because of its symmetric structure [33].…”
Section: Degradation Of Alkanolamine Absorbentsmentioning
confidence: 99%
“…The primary (RNH 2 ), secondary (RNH), and steric hindrance (RNH 2 ) amines are able to form both carbamate and bicarbonate ions. Those amines directly react with CO 2 gases in the zwitterion mechanism (RNHCOO − ), generating bicarbonate ions (HCO 3 − ) and protonated amine (RNH 3 + ), as shown in Equations ( 1) and (2) [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…7 The corrosive activity of organic amine absorbents varies with amine type, amine concentration, acidic gas load and concentration, chemical properties of impurities (typically heat stable salts), and temperature. 5,[8][9][10][11][12][13][14] Xiang et al evaluated the electrochemical behavior of carbon steel in monoethanolamine (MEA) solutions loaded with CO 2 , and studied the influence of factors such as oxygen, thermal stable salts, flow rate, and temperature. The results showed that under MEA/CO 2 conditions, the corrosion rate of carbon steel decreased over time and stabilized at a very low value.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosive activity of organic amine absorbents varies with amine type, amine concentration, acidic gas load and concentration, chemical properties of impurities (typically heat stable salts), and temperature 5,8–14 . Xiang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Even though many different CCS technologies have been proposed to date, only a few have reached commercial status, highlighting CO 2 chemical absorption [5]. Currently, solvents such as ammonia, piperazine and amines have been proposed for their absorption of industrial CO 2 emissions, with commercial focus on the latter group [6,7]. Monoethanolamine (MEA) is one example of a commercial amine with a high capture capacity [8][9][10].…”
Section: Introductionmentioning
confidence: 99%